Estrategias de marketing digital para aumentar las ventas en el Almacén María José. - Dicao Torres, Diana Valeria (2022)
This case study was carried out in the María José warehouse in the city of Babahoyo. whose activity is to offer its customers a variety of products such as clothing for women, men and children, footwear, home decorations and other accessories. In turn, this research aims to define digital marketing strategies to improve their positioning and increase their sales. Marketing strategies are a fundamental tool in business, a true guide and vital for companies that sell products or services, since they allow their managers and leaders to choose and apply the best and most relevant to their needs. In this research, the type of bibliographic research and descriptive research were implemented, which were fundamental for understanding the problems. In addition, the descriptive method, of a qualitative and quantitative nature, was obtained, given that through digital marketing strategies the positive and negative qualities of the María José warehouse were determined, through surveys of the survey, necessary and relevant information was obtained for the investigation.